Accuracy of liver and spleen stiffness on magnetic resonance elastography for detecting portal hypertension: a systematic review and meta-analysis. Issue 2 (10th April 2020) - Singh, Ranjit; Wilson, Mitchell P.; Katlariwala, Prayash; Murad, Mohammad H.; McInnes, Matthew D.F.; Low, Gavin
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: The purpose of this systematic review and meta-analysis was to evaluate the diagnostic accuracy of liver and spleen stiffness on magnetic resonance elastography (MRE) for detecting clinically significant portal hypertension. Methods: A systematic review of MEDLINE, EMBASE, Scopus, the Cochrane Library, and the Grey Literature through to 15 August 2019 was performed. Original articles with >10 patients evaluating liver and/or spleen stiffness on MRE using a reference standard of portal hypertension defined as intractable ascites, esophageal varices, encephalopathy and/or death were included in analysis. Patient, clinical, MRI, and diagnostic performance was independently acquired by two reviewers. Meta-analysis was performed using a bivariate mixed-effects regression model. Results: Fourteen studies were included with 12 studies evaluating liver stiffness and eight studies evaluating spleen stiffness. The pooled and weighted sensitivity, specificity, and area under the curve (AUC) values for liver stiffness on MRE were 83% [95% confidence interval (CI) 72–90%], 80% (95% CI 70–88%), and 88% (95% CI 85–91%), respectively. The pooled and weighted sensitivity, specificity, and AUC values for spleen stiffness on MRE were 79% (95% CI 61–90%), 90% (95% CI 80–95%), and 92% (95% CI 89–94%), respectively. The liver and spleen stiffness sensitivity and specificity values were comparable when evaluating for esophageal varices only at of 80% (95% CI 66–89%) and 76% (95% CI 62–86%) for liver stiffness, and 75% (95% CI 52–90%) and 89% (95% CI 70–96%) for spleen stiffness. Discussion: Liver and spleen stiffness on MRE can serve as a supplemental noninvasive assessment tools for detecting clinically significant portal hypertension. Spleen stiffness may be more specific and accurate than liver stiffness for detecting portal hypertension.